Indonesia EVALUASI PROGRAM PENDIDIKAN MASYARAKAT KELURAHAN BERSIH DARI NARKOBA (BERSINAR) DI BADAN NARKOTIKA NASIONAL KOTA CIMAHI DENGAN MODEL CIPP: EVALUASI PROGRAM PENDIDIKAN MASYARAKAT KELURAHAN BERSIH DARI NARKOBA (BERSINAR) DI BADAN NARKOTIKA NASIONAL KOTA CIMAHI DENGAN MODEL CIPP - Pebriani, Indri; Wahyudin, Uyu (Jurnal Empowerment, 2025)
Drug abuse among the community is currently a serious problem. The crime of drug abuse not only threatens in terms of health, but also threatens in terms of the resilience and security system of a country. The problem of drug abuse in Indonesia is one of the reasons behind the existence of the National Narcotics Agency (BNN). The National Narcotics Agency is one of the efforts made by the government to reduce crimes arising from drug abuse in Indonesia. Now, the National Narcotics Agency is holding a program that seeks to reduce people in drug abuse, especially in Cimahi City. The program is the Kelurahan Bersih dari Obat (Bersinar) program. The Bersinar village program involves various parties, both government, ministries, agencies, legal institutions and community stakeholders. The shining village program includes activities in the fields of prevention, eradication, community empowerment and rehabilitation. To find out the running of the Kelurahan Bersinar program, it is necessary to evaluate the community education program. The evaluation of community education programs used is the Context, Input, Process, Produkct (CIPP) program evaluation model.